A study on effect of PFA on stabilized material using direct shear test - Shakri M.S.; Hafez M.A.; Adnan M.A. (Trans Tech Publications, 2023)
Pulverized fuel ash (PFA) can be classified as hazardous Coal Combustion by-Product (CCP), which can contributes to the environmental pollution. According to (ACAA 2009), USA itself has produced approximately 125.5 million tons per annual of CCP which merely 56 million tons of these waste by-products has been successfully employed in applications and others still remain untreated. Disposal of these materials in landfills can deduce ecological. Thus, finding the solutions and methods of recycling these waste materials are needed, as it can be used as one of the materials in construction projects, engineering purpose or stabilizing process. Therefore, a study on direct shear test have been conducted and the data collected from this study were compared and analyzed through various methods to find out how does PFA works on improving geotechnical properties. © (2014) Trans Tech Publications, Switzerland.